(untitled) (Journal of Pharma Insights and Research, 2026)
Periprosthetic joint infection (PJI) is a primary cause of failure in total knee arthroplasty (TKA), requiring careful management techniques to preserve joint function and mitigate surgical morbidity. Debridement, Antibiotics, and Implant Retention (DAIR) serves as a critical, joint-preserving intervention for early postoperative and acute hematogenous infections. Clinical success with the DAIR protocol ranges between 41% and 92%, a variance heavily influenced by the timing of intervention, the virulence of causative pathogens, and the physiological status of the host. Optimal outcomes are typically achieved when surgical intervention occurs within a narrow window of 4 to 6 weeks following the onset of symptoms, particularly when combined with the exchange of modular components. Conversely, infections involving highly virulent strains such as Staphylococcus aureus or those occurring in elderly patients with significant systemic comorbidities often result in higher rates of treatment failure. The integration of modern diagnostic guidelines, such as the 2021 European Bone and Joint Infection Society (EBJIS) criteria, has refined the precision of diagnostic staging and therapeutic planning. While targeted antibiotic regimens specifically those utilizing rifampin for staphylococcal biofilms are essential components of the protocol, the ideal duration of therapy remains a subject of active investigation. Emerging surgical techniques, including the use of antibiotic pearls and specialized antiseptic irrigation solutions, show promise in enhancing biofilm eradication. Although chronic infections remain a relative contraindication, the application of DAIR in acute care offers superior functional recovery and patient satisfaction compared to more invasive multi-stage revision procedures